2018
DOI: 10.1111/jspn.12218
|View full text |Cite
|
Sign up to set email alerts
|

Ask me: Children's experiences of pain explored using the draw, write, and tell method

Abstract: Children as young as 4 years old can provide detailed accounts of their pain, which extends beyond physical dimensions to include visual, auditory, and sensory features. Nurses need to listen, be honest, and develop trust with children to be helpful. Nonpharmacological pain-relieving strategies can be implemented by parents and nurses in collaboration with the child. Fostering a secure environment is essential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…A study from Turkey found that chest pain among adolescents is associated with depression and impaired emotional and social functioning 12 . Pope et al 13 found that children in pain need to feel secure, and there is a need to support children to engage in activities that they enjoy to help take their minds off their pain. That negative stress is related to pain is found in our study, and is in line with a recent review 14 .…”
Section: Discussionmentioning
confidence: 99%
“…A study from Turkey found that chest pain among adolescents is associated with depression and impaired emotional and social functioning 12 . Pope et al 13 found that children in pain need to feel secure, and there is a need to support children to engage in activities that they enjoy to help take their minds off their pain. That negative stress is related to pain is found in our study, and is in line with a recent review 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Within the context of chronic pain in childhood, one of the main challenges that researchers face is the use of effective tools to access children's views on their lived experiences of pain. The draw, write and tell technique (Angell et al, 2015) appeared to be the most appropriate method for conducting research about pain with children and young people (Pope et al, 2018). This technique focuses on children's own interpretations (Driessnack, 2006) by enabling them to explain their drawings and the words they have written (Pope et al, 2018).…”
Section: The Study: Context and Methodsmentioning
confidence: 99%
“…The draw, write and tell technique (Angell et al, 2015) appeared to be the most appropriate method for conducting research about pain with children and young people (Pope et al, 2018). This technique focuses on children's own interpretations (Driessnack, 2006) by enabling them to explain their drawings and the words they have written (Pope et al, 2018). The draw, write and tell technique has been successfully applied to explore children's perceptions of pain and pain management (Pope et al, 2018); however, this is the first time that the technique is used to study the experience of chronic pain in childhood and adolescence.…”
Section: The Study: Context and Methodsmentioning
confidence: 99%
“…This has important implications in the healthcare setting, as a negative experience may affect future child willingness to actively participate in the procedure, with possible withdrawal, while a positive experience can improve future motivation and engagement [25]. Discussing these problems and our various improvements with the children built trust and allowed them to become stakeholders in improving the research experience [16,18,28,60].…”
Section: Evaluation Of How We Operationalized Reach Principles Into Pmentioning
confidence: 99%
“…We feel that our broader assessment of the emotional and developmental maturity of 4-7 year-olds is justified, at least where a consistent child-centred approach is applied and the concept of dissent is fully factored into the model [11,13,24]. Likewise, children as young as four years have appeared capable of sophisticated description, problem solving and decisional reasoning around treatment in a healthcare facility, when similarly provided with a secure and conducive environment [19,60]. We consider that application of a child-centred approach, including pre-education, familiarisation, playtime and invited participation, could help formulate an appropriate and respectful level of informed assent for this age-group in research and healthcare settings.…”
Section: Informed Assent and Dissentmentioning
confidence: 99%